CRIANÇA ESPERANÇA: comunicação e marketing da Rede Globo - Gallego, Angélica Helena Santini Montes (2007)
This paper has, as a purpose, to analyze the Criança Esperança Project, by Globo Television Network. It attempts to identify whether it is a philanthropic activity through which the company helps the Brazilian society, by reporting the results and informing on the donations divulged by its own media or a Social Marketing Communication Strategy to promote the organization, in addition to helping the community according to the proposed actions and utilizing its Public Relations tools in the Project, in order to consolidate the company s institutional image, by articulating its audience and managing the integrated communication. This research based its conclusions on the analysis on the amounts donated by the show/program viewers; the show/program ratings and the participation of partners and sponsors. These items were trustful indicators for a successful or even unsuccessful communication strategy of the Project. The methodology employed was the Criança Esperança Program/Show Study Case, the document-based bibliographical research and the interviews.